Viscometric Studies of Polybutadiene Based Liquid Rubbers in Benzene and its Derivatives - SHAKIL MUHAMMAD, G.; BALAKRISHNAN, R.; CHANDRASEKAR, R. (Asian Journal of Chemistry, 2010)
Viscosities of the two liquid rubbers poIybutadiene such as hydroxyl taminaled polybutadiene (HTPB) and polybulyl acrylonitrile (PBAN) in four different organic solvents have been determined at various temperatures (303-323 K) ovar the concentration range (0.2-1 %). The temperature and concentration dependences of Ibe shear viscosity of these systems have been discussed. An equation that reproduces tile viscosity as a function of temperature and concentration has been developed. The activation parameters of viscosity have also been calculated.